Genetic Divergence for Yield and Yield-Contributing Traits in Cucumber (Cucumis sativus L.) - H R Sharma (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2006)
The cluster analysis grouped the thirty one genotypes of cucumber, collected from different sources in India, into seven clusters. The genotypes Jorji Local, Bengal 60, JJL and Derabassi Local were promising with respect to yield per plant and fruit length, while Gyn-2, Gyn-3 and Gyn-4 were superior for number of fruits per plant. However, genotypes Chakkimore local, Farukabad Local, Chamoli Local and Chamba Local were promising for average fruit weight and fruit breadth.